Burkholderia cepacia Bacteremia Complicated by Intracranial Abscesses and Immune Reconstitution Inflammatory Syndrome in a Renal Transplantation Recipient - Vijoy Kumar Jha; Debasish Mahapatra; Arivalagan Balakrishnan; R Chandran (Saudi Journal of Kidney Diseases and Transplantation, 2022)
Burkholderia cepacia is almost always a colonizing organism rather than an infecting organism, but it may be pathogenic in immunocompromised individuals when isolated from body fluids that are ordinarily sterile. When recovered from blood culture it may present infection, pseuedo infection, or actual infection from contaminated intravenous fluids. We present a case of a renal transplant recipient patient who developed B. cepacia bacteremia following central venous cannulation. The subsequent clinical course was of worsening quadriparesis, which on neuroimaging revealed multiple brain and spinal abscesses. Following two weeks of intravenous antibiotics, his clinical features further worsened and the size of lesions further increased, which was suggestive of immune reconstitution inflammatory syndrome. With an increased steroid dose and continuation of the same anti-biotics, there was a regression of the lesions and significant clinical improvement.